Kebijakan Pesantren Mu’adalah dan Implementasi Kurikulum di Madrasah Aliyah Salafiyah Pondok Tremas Pacitan - Ara Hidayat; Eko Wahib (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2014)
This study is abaut the Mu’adalah Boarding School Policy and the Implementation of curriculum at the Islamic Senior High School (Madrasah Aliyah) Salafi Tremas Pacitan. The educational institution of the Islamic boarding school is an inseparable part of the nationally educational system. This changes the minset and point of view of the previous Islamic boarding school that was considered as a non-formal institution that did-not get good appreciation of its graduates. The research findings show that the mua’adah Islamic boarding shcool has been established as an institution that is equivalent to other formal educational institutions by the ministry of religious. The status of Salafiyah Islamic senior high school is stronger. Furthemore, it must be improved directly its educational quality, teacher competences, and the curriculum implementation of theIslamic Senior High School of Salafiyah Tremas Pacitan.